A three‐dimensional CFD and experimental study to optimize naturally air‐cooled electronic equipment enclosure: Effects of inlet height, heat source position, and buoyancy on mean rise in temperature. Issue 1 (17th October 2017) - Riaz, Ali; Basit, Abdul; Ibrahim, Adnan; Shah, Ajmal; Basit, Muhammad Abdul
Abstract: The major reason behind failure of electronic components is the rise in temperature. To optimize design of naturally cooled electronic equipment enclosure, a detailed experimental study and a computational fluid dynamics (CFD) analysis were performed. Commercially available software, ANSYS Fluent, was used for CFD analysis. The three‐dimensional form of Navier–Stokes equations was used to solve the problem computationally. Aluminium enclosure having dimensions of 40 cm × 40 cm × 21 cm and thermal conductivity of 210 W/m·K were manufactured for experimentation in this research study. Electronic components were modelled as constant heat flux body during experimentation and CFD analysis. Effect of heat source vertical and horizontal position, inlet height, and buoyancy effect on mean rise in temperature inside the aluminium enclosure was studied. Mean temperature inside the casing was increased by increasing either heat source height or inlet height. At the end, computational results were compared with experimental results in order to check the validity of results. Computational results were highly in accordance with experimental results, because maximum percentage difference between experimental and CFD results was less than 6%. On the basis of results obtained from experiments and simulations, the best configuration of heat source and inlet was proposed, which will provide optimum thermal performance. Numerical results of velocity and temperature inside the enclosure were plotted in the form of streamlines and isotherms. This study can be used as a fundamental step prior to designing electronic equipment enclosure.